Correlation between surface chemistry and magnetism in iron nanoparticles. Issue 15 (29th June 2021) - Haim, Lorraine; Robert, François; Peres, Laurent; Lecante, Pierre; Philippot, Karine; Poteau, Romuald; Respaud, Marc; Amiens, Catherine
Abstract : Amido and hydrides ligands govern stability and magnetic properties of iron nanoparticles: magnetization could be an indicator of reactivity. Abstract : To shed light on the factors governing the stability and surface properties of iron nanoparticles, a series of iron nanoparticles has been produced by hydrogenation of two different iron amido complexes: the bis[bis(trimethylsilyl)amido] Fe(ii ), [Fe(N(SiMe3 )2 )2 ]2, and the bis(diphenylamido) Fe(ii ), [Fe(NPh2 )2 ]. Nanostructured materials of bcc structure, or nanoparticles displaying average sizes below 3 nm and a polytetrahedral structure, have been obtained. Depending on the synthesis conditions, the magnetization of the nanoparticles was either significantly lower than that of bulk iron, or much higher as for clusters elaborated under high vacuum conditions. Unexpectedly, hydrogenation of aromatic groups of the ligands of the [Fe(NPh2 )2 ] precursor has been observed in some cases. Confrontation of the experimental results with DFT calculations made on polytetrahedral Fe91 model clusters bearing hydrides, amido and/or amine ligands at their surface, has shown that amido ligands can play a key role in the stabilisation of the nanoparticles in solution while the hydride surface coverage governs their surface magnetic properties. This study indicates that magnetic measurements give valuable indicators of the surface properties of iron nanoparticles in this size range, and beyond, of their potential reactivity.